Determination of all hydrodynamic added properties resulting from fluid structure interactions using singular value decomposition - Raisee, Mehrdad; Cervantes, Michel J. (Journal of fluids and structures, 2023)
The hydrodynamic added effects such as inertia, damping and stiffness resulting from a fluid flow surrounding a structure strongly affect its dynamic response. Thus, accurate determination of such effects is of prime importance in the design of modern mechanical systems exposing fluid–structure interactions. The main goal of this study is to develop a unified methodology for the simultaneous identification of all hydrodynamic added effects caused by fluid–structure interactions. The proposed model is based on the least squares solution of an over-determined system of equations using singular value decomposition. The singular value decomposition determine the added inertia and stiffness without any assumption on their respective magnitude and variation, necessary for other methods. The method is firstly validated using the analytical solutions for single degree of freedom free vibration and forced oscillations under single and multiple frequency excitations for a variety of cases. It is found that the proposed method can predict all presumed added properties for transient forced oscillations under single and multiple external forces. Next, the method is applied to two challenging fluid structure interaction test studies; an oscillating hydrofoil in a turbulent flow and a Kaplan turbine runner subjected to single and multiple frequency perturbations. In both cases, the results of the proposed method are found to be consistent with results of methods in the literature and confirmed the underlying hypothesis of their analysis. The results confirm the ability of the newly developed methodology in evaluation all fluid added effects in complex engineering turbulent flows subject to one to several excitations, simultaneously. •A novel methodology for identification of all fluid added properties is proposed.•The methodology performs well in identification of the fluid added properties, assuming the fluid added stiffness is small.•The developed methodology is based on the least squares solution and singular value decomposition methods.•The methodology is applied to two CFD problems: (i) an oscillating hydrofoil and (ii) a Kaplan turbine runner.•The results of the proposed method are in excellent agreement with results of alternative methods in the literature.